The Efforts Of Prevent Covid-19 In The People of Kalimantan, Indonesia - Rudi, Abil; Yetiani, Novin; Sunarti; Damayanti, Ria; Masan, Lea; Montessori, Yolanda; Kurniati, Paskalia Tri; Pratama, Rika Yuanita (Fakultas Kedokteran, Universitas Papua, 2024)
Since the coronavirus disease 2019 (COVID-19) pandemic in December 2019, it has brought some significant lifestyle changes to people around the world. This research is about the prevention efforts made by the community in West Kalimantan, Indonesia against the spread of COVID-19. Data collection through questionnaires distributed online for 3 months in 2021. Respondents in this study were the people of West Kalimantan, Indonesia. Most respondents have high prevention efforts regarding hand washing, wearing masks, maintaining distance, avoiding crowds, and reducing physical mobility to avoid COVID-19 infection. Most of the respondents also showed good knowledge in identifying the basic symptoms of COVID-19. Respondents mostly have a good attitude towards the spread of COVID-19. These findings provide insight into efforts to prevent COVID-19 among the people of West Kalimantan and can help the government make policies to control the spread of COVID-19, as well as other new infections in West Kalimantan, Indonesia.